THE EFFECT OF SCARIFICATION TECHNIQUE WITH FERMENTATION AND DEOPEROCOLATION METHODS ON SUGAR PALM SEEDS WITH PERCENT SURROUNDING PARAMETERS - Paksi Arenda Ayatullah Dewantara; Duryat Duryat; Trio Santoso (Journal of People, Forest and Environment, 2022)
Sugar palm (Arenga pinnata) is a palm plant that has many benefits but has a hard seed coat and is impermeable to water and oxygen. besides that the palm skin also contains ligin so that the seeds is dormant. Proper scarification technique needs to be done to overcome the dormancy in the palm seeds. Fermentation and deopercolation are scarification methods used to break the dormancy period of palm seeds. The purpose of this study was to determine the scarification method to break the dormancy period of sugar palm seeds by using the percent germination parameter. Fermentation was carried out with cow dung tested for 0.2, 4, 6 weeks. While deopercolation was carried out using sandpaper with a paper roughness level of 80, sanding was carried out on the backs of the palm seeds where the roots would appear. Each treatment was repeated three times in each replication using 15 sugar palm seeds. This research was conducted for 2 months in the greenhouse of the Faculty of Agriculture, University of Lampung. The results showed that the best treatment was the fermentation method for 6 weeks combined with deopercolation with a germination percentage value of 82.22%. The use of abrasive paper for the deopercolation method needs further research, the results of this study can be used in the practice of sugar palm cultivation